Amphiphilic Single-Chain Polymer Nanoparticles as Imaging and Far-Red Photokilling Agents for Photodynamic Therapy in Zebrafish Embryo Xenografts - İŞCİ, ÜMİT; ŞAHİN, ZEYNEL (My University, 2024)
This work introduces rationally designed, improved amphiphilic single-chain polymer nanoparticles (SCNPs) for imaging and photodynamic therapy (PDT) in zebrafish embryo xenografts. SCNPs are ultrasmall polymeric nanoparticles with sizes similar to proteins, making them ideal for biomedical applications. Amphiphilic SCNPs result from the self-assembly in water of isolated synthetic polymeric chains through intrachain hydrophobic interactions, mimicking natural biomacromolecules and, specially, proteins (in size and when loaded with drugs, metal ions or fluorophores also in function). These ultrasmall, soft nanoparticles have various applications, including catalysis, sensing, and nanomedicine. Initial in vitro experiments with nonfunctionalized, amphiphilic SCNPs loaded with a photosensitizing Zn phthalocyanine with four nonperipheral isobutylthio substituents, ZnPc, showed promise for PDT. Herein, the preparation of improved, amphiphilic SCNPs containing ZnPc as highly efficient photosensitizer encapsulated within the nanoparticle and surrounded by anthracene units is disclosed. The amount of anthracene groups and ZnPc molecules within each single-chain nanoparticle controls the imaging and PDT properties of these nanocarriers. Critically, this work opens the way to improved PDT applications based on amphiphilic SCNPs as a first step toward ideal, long-term artificial photo-oxidases (APO).
Keywords: Tıp; Biyomedikal Mühendisliği; Sağlık Bilimleri; Mühendislik ve Teknoloji; Medicine; Biomedical Engineering; Health Sciences; Engineering and Technology; Klinik Tıp (MED); Mühendislik, Bilişim ve Teknoloji (ENG); Klinik Tıp; Mühendislik; Malzeme Bilimi; TROPİKAL TIP; MALZEME BİLİMİ, BİYOMATERYAL; MÜHENDİSLİK, BİYOMEDİKAL; Clinical Medicine (MED); Engineering, Computing & Technology (ENG); CLINICAL MEDICINE; ENGINEERING; MATERIALS SCIENCE; TROPICAL MEDICINE; MATERIALS SCIENCE, BIOMATERIALS; ENGINEERING, BIOMEDICAL; Biyomalzemeler; Fizik Bilimleri; Biyomedikal mühendisliği; Farmasötik bilim; Yaşam Bilimleri; Biomaterials; Physical Sciences; Pharmaceutical Science; Life Sciences; anthracene; imaging; photodynamic therapy; phthalocyanins; single-chain nanoparticles; zebrafish embryos